1992
DOI: 10.1038/jcbfm.1992.87
|View full text |Cite
|
Sign up to set email alerts
|

Evoked Neuronal Activity Accompanied by Transmitter Release Increases Oxygen Concentration in Rat Striatum in vivo but Not in vitro

Abstract: Dopamine and oxygen (O2) were measured in the caudate nucleus of anesthetized rats and in striatal slices during electrical stimulation. Simultaneous electrochemical detection of dopamine and O2 was accomplished with fast-scan cyclic voltammetry at a Nafion-coated carbon-fiber microelectrode. Stimulation of the medial forebrain bundle resulted in synaptic overflow of dopamine in the caudate nucleus. At the same time, O2 concentration increased in the extracellular fluid with two separate phases. The amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 44 publications
5
36
0
Order By: Relevance
“…Assuming a maximum ECF concentration of 50 vmol/l, the above concentrations represent mean percentage increases of 889 15% and 5099% for tail pinch and grooming, respectively. Although O 2 utilisation increases during stimulated neuronal activity, the present results confirm previous findings that the rise in rCBF exceeds the increase in O 2 utilisation resulting in a net increase in O 2 (Leniger-Follert and Lü bbers, 1976;Fox et al, 1988;Zimmerman et al, 1992). For this reason O 2 currents provide an index of increases in rCBF only when such increases exceed O 2 utilisation.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Assuming a maximum ECF concentration of 50 vmol/l, the above concentrations represent mean percentage increases of 889 15% and 5099% for tail pinch and grooming, respectively. Although O 2 utilisation increases during stimulated neuronal activity, the present results confirm previous findings that the rise in rCBF exceeds the increase in O 2 utilisation resulting in a net increase in O 2 (Leniger-Follert and Lü bbers, 1976;Fox et al, 1988;Zimmerman et al, 1992). For this reason O 2 currents provide an index of increases in rCBF only when such increases exceed O 2 utilisation.…”
Section: Resultssupporting
confidence: 88%
“…Carbon electrodes are also more stable and in the case of CPEs have been found to be stable over several months in vivo (O'Neill and Fillenz, 1985). Recently, a new method for the measurement of dissolved O 2 in vivo involving Nafion™ modified carbon fibre disk electrodes (CFEs) and fast cyclic voltammetry has been reported by Wightman's group (Zimmerman and Wightman, 1991;Zimmerman et al, 1992). As a fastscan technique this method also has advantages associated with subsecond time resolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulationinduced decreases in radioligand binding likely reflect changes in extracellular DA levels rather than alterations in cerebral blood flow (CBF). Simultaneous measurements of DA levels and oxygen consumption in the rat striatum have shown an elevation of local CBF during stimulation of the MFB in vivo (Zimmerman et al 1992). In another study, Chugani et al (1988) showed that CBF was not altered in the striatum following electrical nigrostriatal stimulations as measured with [ 14 C]iodoantipyrine.…”
Section: Discussionmentioning
confidence: 97%
“…at ASPET Journals on May 9, 2018 jpet.aspetjournals.org detected by carbon fiber electrodes and change in the striatum after MFB stimulation (Zimmerman and Wightman, 1991;Zimmerman et al, 1992;Cramer et al, 1997;Venton et al, 2003). DA oxidation and oxygen reduction occur at different potentials (ϩ0.3 and Ϫ1.4 V, respectively) (Zimmerman et al, 1992;Venton et al, 2003) and show a different kinetic response (Venton et al, 2003), ruling out the oxygen involvement on type II.…”
Section: The Fountain-drain Striatal Matrix 39mentioning
confidence: 99%